Stopping power of the 12C carbon nucleus for a projectile in p12C collisions at a momentum of 4.2 GeV/s (Eurasian Journal of Physics,Chemistry and Mathematics, 2026)
In this paper, the stopping power of carbon nuclei in interactions of protons with a momentum of 4.2 GeV/s with carbon nuclei is studied, based on the study of multiple spectra of secondary charged particles, π- mesons, π+ mesons and protons of the participants depending on the degree of centrality. The obtained experimental data are compared with the calculations of the theoretical CEM model (cascade-evaporation model) and the FRITIOF model with and without taking into account Δ+ and Δ0-isobars. It is shown that in central interactions the primary proton loses a significant part of its energy and the fraction of leading protons increases, while the fraction of target protons is maximal in events with Q = 1 and decreases rapidly in events with Q ≥ 5. This result reflects the softening of the spectrum of fast target protons as the centrality of collisions increases.